Development of the International Cardiac Rehabilitation Registry Including Variable Selection and Definition Process - Mohiul I. Chowdhury; Karam Turk-Adawi; Abraham Samuel Babu; Gabriela Lime de Melo Ghisi; Pamela Seron; Tee Joo Yeo; Jamal Uddin; Martin Heine; Marianna Garcia Saldivia; Evangelia Kouidi; Masoumeh Sadeghi; Raghdah Aljehani; et al. (Ubiquity Press, 2022)
Introduction: The International Council of Cardiovascular Prevention and Rehabilitation (ICCPR) is developing a registry (ICRR) specifically for low-resource settings, where the burden of cardiovascular diseases is greatest and the need for program development highest. Herein we describe the development process, including the variable selection process. Method: Following a literature search on registry best practices, a stepwise model for ICRR development was identified. Then, based on recommendations by Core Outcome Set-STAndards for Development (COS-STAD), we underwent a process to identify variables. All available CR registries were contacted to request their data dictionaries, reviewed CR quality indicators and guideline recommendations, and searched for common data elements and core outcome sets; 35 unique variables (including patient-reported outcomes) were selected for potential inclusion. Twenty-one purposively-identified stakeholders and experts agreed to serve on a Delphi panel. Panelists rated the variables in an online survey, and suggested potential additional variables; A webcall was held to reach consensus on which to include/exclude. Next, panelists provided input to finalize each variable definition, and rated which associated indicators should be used for benchmarking in registry dashboards and a patient lay summary; a second consensus call was held. A 1-month public comment period ensued. Results: First, registry objectives and governance were approved by ICCPR, including data quality and access policies. The protocol was developed, for public posting. For variable selection, the overall mean rating was 6.1 ± 0.3/7; 12 were excluded, some of which were moved to a program survey, and others were revised. Two variables were added in an annual follow-up, resulting in 13 program and 16 patient-reported variables. Legal advice was sought to finalize ICRR agreements. Ethics approvals were obtained. Usability testing is now being initiated. Conclusion: It is hoped this will serve to harmonize CR assessment internationally and enable quality improvement in CR delivery in low-resource settings.